Between body esteem and mental health among adolescents in China - Wu, Ning; Prihadi, Kususanto Ditto (International Journal of Public Health Science (IJPHS), 2024)
Numerous studies have highlighted the importance of body esteem and unconditional self acceptance (USA) in promoting mental health over actual body shape. This study aimed to examine the relationship between body esteem and mental health, and whether this is mediated by USA, and whether the mediation is moderated by actual body shape. The cross-sectional study included 189 adolescents from Ganzhou, China, to complete the body esteem scale (BES) and general health questionnaire (GHQ-28) to measure body esteem and general mental health, respectively. The bootstrap analysis, with 5,000 samples at a 95% confidence interval showed that the effect of body esteem on mental health was fully mediated by USA, and the significant mediation effect was observed only among individuals with moderate body mass index (BMI). These findings suggest that unconditional self-acceptance is an important protective factor against mental health issues, yet striving to have a moderate BMI with positive attitude helps with the entire process.